Why do businesses grow faster in urban areas than in rural areas? - LEE, Jungho (Institutional Knowledge at Singapore Management University, 2020)
We document that growth of business earnings is mostly observed among young ﬁrmsin metro areas. Three explanations are considered: metro areas attract more-productiveentrepreneurs, and reaching the optimal size takes time due to borrowing constraints;metro areas provide better learning opportunities; and high operating costs in metroareas allow only the productive ﬁrms to survive. We use a ﬁrm-dynamics model with alocation choice to quantify the extent to which the three theories explain the data. Weﬁnd the ﬁrst two theories largely explain the high growth among metro, young ﬁrms. Ourmodel also suggests the distortion in entrepreneurs’ location choice can induce substantialwelfare loss.